Advancing pain education: a cross-sectional study in the Portuguese medical schools - Joana Cristina Ferreira Mendes de Castro Bento; Isaura Tavares; Daniel Humberto Pozza (BMC Medical Education)
Abstract Introduction Chronic pain negatively impacts on quality of life and is often underreported and undertreated. Therefore, it is essential for medical schools to provide education in pain management for students. This study evaluated the current state of pain education in the Portuguese medical schools, focusing on integrating pain-related topics into the curriculum. Methods A cross-sectional study was employed, involving all the eight public medicals schools in Portugal. The study, approved by the Ethics Committee of the Faculty of Medicine of the University of Porto, utilized a previous validated questionnaire sent via electronic mail. The data collection spanned from January 2023 to October 2023, and responses were analysed using the SPSS software for descriptive statistics. Results All eight public medical schools responded to the questionnaire, providing insights into their pain education practices. Over the six years of medical education, 50% of the schools offered dedicated course content on chronic pain within the curriculum. This instruction is primarily provided in the second year, with variations in the hours for both theoretical and practical teaching. Additionally, 62.5% integrate pain-related topics into other discipline-based courses, predominantly in the fourth year. Post-graduate pain education activities were reported in only three of the eight schools (37.5%). Conclusions These findings represent the first analysis of pain education in public Portuguese Medical Schools. The findings indicate that enhancements in pain education through the introduction of mandatory pain topics, curriculum integration, and investment in post-graduation courses are needed. These improvements aim to provide medical students the essential knowledge and skills to proficiently manage the intricate challenges of chronic pain, thereby enhancing patients’ quality of life and reducing social burdens.